Chemical pleurodesis using mistletoe extracts via spray catheter during medical thoracoscopy for management of malignant pleural effusion. Issue 3 (14th March 2017) - Eom, Jung Seop; Kim, Tae Hwa; Lee, Geewon; Ahn, Hyo Yeong; Mok, Jeong Ha; Lee, Min Ki
Abstract : We present three cases of successful chemical pleurodesis with a liquid solution of mistletoe extract using a spray catheter during medical thoracoscopy. The medical thoracoscopy was performed in all presented cases to remove pleural effusion and conduct chemical pleurodesis to manage symptomatic malignant pleural effusion. A spray catheter was used to instil the mistletoe extract evenly into the pleural cavity, and there were no pleurodesis‐related complications. Respiratory symptoms caused by pleural effusion improved after pleurodesis, and successful pleurodesis was maintained for more than 3 months after medical thoracoscopy in all three patients. Abstract : We present three cases of successful chemical pleurodesis with a liquid solution of mistletoe extract using a spray catheter during medical thoracoscopy.